1984
DOI: 10.1139/x84-163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clear-cutting on the vegetation and soil of an eastern hemlock dominated ecosystem, western Upper Michigan

Abstract: The effects of clear-cutting on the vegetation and soil of an ecosystem dominated by eastern hemlock (Tsugacanadensis (L.) Carr.) were studied at four locations along the boundaries of the Sylvania Recreation Area (Ottawa National Forest) in western Upper Michigan, U.S.A. The position of commercially clear-cut areas along the boundaries of the relatively undisturbed 8500-ha tract provided the opportunity to examine the probable effects of clear-cutting after an average of 46 years afterward. Clear-cutting resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…The question of fire is problematic in relation to hemlock-dominated forests. Although there is evidence of fire-initiated hemlock stands (Maissurow 1941;Hix and Barnes 1984;Spies and Barnes 1985), mature eastern hemlock may be the least fire tolerant species of mesic forests of the northern Lakes States with thin bark and shallow root systems (Rogers 1978). Frelich and Lorimer (1991) stated that even during conditions of very low humidity, fires in mesic forests in the northern Lake States smolder in the duff layer and cause little overstory mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The question of fire is problematic in relation to hemlock-dominated forests. Although there is evidence of fire-initiated hemlock stands (Maissurow 1941;Hix and Barnes 1984;Spies and Barnes 1985), mature eastern hemlock may be the least fire tolerant species of mesic forests of the northern Lakes States with thin bark and shallow root systems (Rogers 1978). Frelich and Lorimer (1991) stated that even during conditions of very low humidity, fires in mesic forests in the northern Lake States smolder in the duff layer and cause little overstory mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, they show that high-severity disturbances, including natural fire in blowdown slash and clear-cutting followed by slash burning or scarification of the soil, lead to conversion of northern hardwoods-hemlock to aspen (Populus tremuloides) and paper birch (Betula papyrifera) (Stoeckeler 1948;Graham and others 1963;Fralish 1972;Frelich and Lorimer 1991); that moderate-severity disturbances including surface fire, heavy canopy windthrow, and canopy clear-cut with minimal understory disturbance can maintain the predisturbance composition-either hemlockhardwood or aspen-paper birch (Zon and Scholz 1929;Shirley 1931Shirley , 1932Zehngraff 1949;Erye and Zillgitt 1953;Hubbard 1972;Frelich and Lorimer 1991)-and that low-severity to moderate-severity disturbances including selection cutting, spot fire, and blowdown allow forests to remain as hemlockhardwood or cause disturbance-mediated accelerated succession from aspen-birch to northern hardwood-hemlock (Eyre and Zillgitt 1953;Heinselman 1954;Tubbs 1977;Frelich and Lorimer 1991;Abrams and Nowacki 1992;Frelich and Graumlich 1994). Hix and Barnes (1984) report a major fluctuation in the hemlock to sugar maple ratio after clear-cut logging, but their study area is still dominated by these species. As a whole, these studies verify the dynamics shown in Figure 4A for states 1 and 2, including switches between hemlock-hardwood and aspen forest types.…”
Section: The Conceptual Model and Dynamics Of Three Systemsmentioning
confidence: 99%
“…The left and right y axes are complimentary to each other and show forest canopy composition (percent basal area or density of stems) in ordered categories after disturbance (3-30 years after disturbance for stands dominated by aspenpaper birch, and 20-50 years after disturbance for stands dominated by hardwood-hemlock). Stands that were hardwood-hemlock dominated both before and after disturbance (᭡) are from case studies by Zon and Scholz (1929), Zillgitt (1950, 1953), Tubbs (1977), Hix and Barnes (1984), Frelich and Lorimer (1991), and Frelich and Graumlich (1994). Stands that were dominated by hardwood-hemlock prior to disturbance, but aspen-paper birch after disturbance (᭹), are from case studies by Stoeckeler (1948), Graham and others (1963), and Frelich and Lorimer (1991).…”
Section: Categories Of Forest Dynamicsmentioning
confidence: 99%
“…The objective in the selection system for post-cut basal area is 18 m 2 /ha of trees > 10 cm dbh and this increases to about 28 m 2 / ha before the next cut cycle in 20 to 25 years (Corbett 2000). This is less than that reported for old-growth northern hardwoods, which is typically > 35 m 2 / ha (Lutz 1930a, Morey 1936, Dunn et al 1983, Hix and Barnes 1984, Keddy 1994. It is also less than that reported in protected zones of the Park by Smith (1977) (38-58 m 2 /ha) and Voigt and Addison (2000) (39 m 2 /ha).…”
Section: Small (Treefall) Gapsmentioning
confidence: 64%